Het Amsterdams Perikopenboek : Volkstalige vroomheid in veertiende-eeuws Vlaanderen. - Jonker, Esther, 1980- (LUP Dissertaties., 2010)
Manuscript Amsterdam, UB, I G 41 (also known as the Amsterdam lectionary; Amsterdamus lectionarium; here referred to as Amsterdam pericope book) has never received through scholarly attention. This thesis aims to fill the gap by positioning the manuscript within the corpus of Middle Dutch literature by analyzing all aspects for reconstructing the historical context of the book.